Influenza virus RNA polymerase: insights into the mechanisms of viral RNA synthesis - te Velthuis, Aartjan J.W. (Nat Rev Microbiol, 2016)
The genome of influenza viruses consists of multiple segments of single stranded negative-sense RNA. Each of these segments is bound by the heterotrimeric viral RNA-dependent RNA polymerase and multiple copies of nucleoprotein, forming viral ribonucleoprotein (vRNP) complexes. It is in the context of these vRNPs that the viral RNA polymerase carries out transcription of viral genes and replication of the viral RNA genome. In this Review, we discuss our current knowledge of the structure of the influenza virus RNA polymerase, how it carries out transcription and replication, and how its activities are modulated by viral and host factors. Furthermore, we discuss how advances in our understanding of polymerase function could help identifying new antiviral targets.